Cultivation and Genome Sequencing of Bacteria Isolated From the Coffee Berry Borer (Hypothenemus hampei), With Emphasis on the Role of Caffeine Degradation - Vega, Fernando E.; Emche, Sarah; Shao, Jonathan; Simpkins, Ann; Summers, Ryan M.; Mock, Meredith B.; Ebert, Dieter; Infante, Francisco; Aoki, Sayaka; Maul, Jude E. (Frontiers in Microbiology, 2021)
The coffee berry borer, the most economically important insect pest of coffee worldwide, is the only insect capable of feeding and reproducing solely on the coffee seed, a food source containing the purine alkaloid caffeine. Twenty-one bacterial species associated with coffee berry borers from Hawai’i, Mexico, or a laboratory colony in Maryland (Acinetobacter sp. S40, S54, S55, Bacillus aryabhattai, Delftia lacustris, Erwinia sp. S38, S43, S63, Klebsiella oxytoca, Ochrobactrum sp. S45, S46, Pantoea sp. S61, Pseudomonas aeruginosa, P. parafulva, and Pseudomonas sp. S30, S31, S32, S37, S44, S60, S75) were found to have at least one of five caffeine N-demethylation genes (ndmA, ndmB, ndmC, ndmD, ndmE), with Pseudomonas spp. S31, S32, S37, S60 and P. parafulva having the full complement of these genes. Some of the bacteria carrying the ndm genes were detected in eggs, suggesting possible vertical transmission, while presence of caffeine-degrading bacteria in frass, e.g., P. parafulva (ndmABCDE) and Bacillus aryabhattai (ndmA) could result in horizontal transmission to all insect life stages. Thirty-five bacterial species associated with the insect (Acinetobacter sp. S40, S54, S55, B. aryabhattai, B. cereus group, Bacillus sp. S29, S70, S71, S72, S73, D. lacustris, Erwinia sp. S38, S43, S59, S63, K. oxytoca, Kosakonia cowanii, Ochrobactrum sp. S45, S46, Paenibacillus sp. S28, Pantoea sp. S61, S62, P. aeruginosa, P. parafulva, Pseudomonas sp. S30, S31, S32, S37, S44, S60, S75, Stenotrophomonas sp. S39, S41, S48, S49) might contribute to caffeine breakdown using the C-8 oxidation pathway, based on presence of genes required for this pathway. It is possible that caffeine-degrading bacteria associated with the coffee berry borer originated as epiphytes and endophytes in the coffee plant microbiota.